Utility Regulation and Risk Allocation: The Roles of Marginal Cost Pricing and Futures Markets. - Cowan, S (Department of Economics (University of Oxford), 2002)
The paper assesses the welfare effects of different ways of allocating input price risk between a regulated utility, consumers and speculators in a futures market. A risk-averse utility setting a fixed retail price requires a price that exceeds expected marginal cost, unless an efficient futures market is available. The firm bears no risk when input price risk is transferred to consumers, but consumers may not like price risk. When a futures market is available to consumers marginal cost pricing is always preferable to a fixed retail price. The policy conclusion is that marginal cost pricing should be combined with the development of futures markets in which consumers can hedge.